Chopin as Romantic narrator (in his youth) - Nowicka, Justyna Cecylia (Interdisciplinary Studies in Musicology, 2018)
One can find the same features in Chopin’s correspondence as in his music. They share a wealth of emotions, expressivity and lightness, and also narrative and speech-like qualities. Far from programmicity and illustrative explicitness, Chopin the composer articulates musical content with an almost verbal force of transmission; his letters, meanwhile, bear the same distinct stamp of his personality that marks out his piano works. In both domains, Chopin may be called a narrator, but particularly interesting proves to be analysis of his correspondence, from the point of view of the narration of a Romantic ironical poem. Although one would be hard pressed to speak of an exact equivalence, it is worth taking into account the strong subjectivity, combined with irony and the writer’s self-irony, but above all his affinity with Schlegelian Romantic irony. This notion is of fundamental significance for changes to the subject in Romantic poetry and for the emergence of the form of the ironical poem. The creativeness of the text, the exposure of the subject, digressions, humour, leaps of thought and style, and a variability and transformation of content - those are just some of the characteristics of the ironical narrator. Also crucial to these considerations is the Romantic aesthetic of the fragment.